An umbrella review of the available evidence syntheses to inform vaccination practices and policies for the COVID-19 pandemic in Africa - Els, Krisna (Department of Public Health and Family Medicine, 2024)
Background: In Africa, the rollout of COVID-19 vaccines lags other continents. The rollout in Africa started in the latter part of the first quarter of 2021 compared with earlier periods in high income settings. Optimal COVID-19 vaccination rollout in Africa should be guided by context-specific and up to date evidence. We conducted an umbrella review to identify, analyze and characterize the evidence syntheses that is available and has the potential to inform COVID-19 vaccination practices and policies in Africa. Methods: A systematic search for scoping reviews, systematic reviews, rapid reviews, and meta-analyses was performed in PubMed/Medline, Web of Science, Scopus (EMBASE), Epistemonikos and The Cochrane Library. Search outputs were exported to Rayyan software for screening. From the included studies, predefined outcomes were extracted and recorded on a data extraction form. Study characteristics, number and types of evidence syntheses were reported. Pooled results from the included studies were reported, including the statistical methods used. Where pooling of reported results had not been done and was feasible to do so, we conducted our own data pooling. Results: A total of 1111 papers were retrieved from all the databases. After removing duplicates and screening for inclusion, 15 papers were included: systematic reviews (n=4), systematic reviews and meta-analysis (n=7), meta-analysis alone (n=2), rapid review and meta- analysis (n=1), and a review of surveys (n=1). Results from the included studies were from 36 (66%) out of 55 African countries. The most abundant evidence was on the seroprevalence of antibodies against SARS-CoV-2 which ranged from 8.2% (95% CI: 0.8-22.3%) to 22% (95% CI 14%-31%). Conclusions: At the time of conducting this study, there was paucity of systematized evidence from majority of the African countries. Evidence syntheses gaps were evident for the incidence and severity of COVID-19 related outcomes, including hospitalization and mortality, as well as vaccine acceptance rates. Open Science Framework Registration: 10.17605/OSF.IO/PTB9W